2004
DOI: 10.1023/b:cemn.0000022776.47302.ce
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor- 1 Upregulates the Tight Junction and P-glycoprotein of Brain Microvascular Endothelial Cells

Abstract: 1. The present study was aimed at elucidating effects of transforming growth factor-beta (TGF-beta) on blood-brain barrier (BBB) functions with mouse brain capillary endothelial (MBEC4) cells. 2. The permeability coefficients of sodium fluorescein and Evans blue albumin for MBEC4 cells and the cellular accumulation of rhodamine 123 in MBEC4 cells were dose-dependently decreased after a 12-h exposure to TGF-beta1 (0.01-10 ng/mL). 3. The present study demonstrates that TGF-beta lowers the endothelial permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 18 publications
6
64
0
Order By: Relevance
“…It was reported that expression of occuludin, one of the transmembrane tight junction proteins, was not changed by exposure of ECs to shear stress of 1.5 Pa (28) . However, it was showed that TGF-ß1 synthesized by SMCs upregulated tight junctions (29) and its synthesis in CM may be increased by cellular interactions with ECs under shear conditions. Both shear stress and cellular interactions between ECs and SMCs may induce the tight junction formations and lead to the reduction of the EC permeability in CM.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that expression of occuludin, one of the transmembrane tight junction proteins, was not changed by exposure of ECs to shear stress of 1.5 Pa (28) . However, it was showed that TGF-ß1 synthesized by SMCs upregulated tight junctions (29) and its synthesis in CM may be increased by cellular interactions with ECs under shear conditions. Both shear stress and cellular interactions between ECs and SMCs may induce the tight junction formations and lead to the reduction of the EC permeability in CM.…”
Section: Discussionmentioning
confidence: 99%
“…In the CNS, TGF-b is neuroprotective, and in vitro studies have shown its capacity to induce Mdr1 activity and to reduce BBB permeability (Dohgu et al 2004). TGF-b is secreted by astrocytes and CNS-ECs, and TGF-b known to downregulate the extent of leukocyte transmigration across the endothelium.…”
Section: Regulation Of the Bbb By Astrocytesmentioning
confidence: 99%
“…67 Some pericytes-derived mediators also exert a modulating influence on BBB function by regulating the expression of endothelial junction proteins. There include transforming growth factor-beta1 (TGF-beta1), 68 glial cell-derived neurotrophic factor (GDNF), 69 and angiopoietin 1 (ANG-1).…”
mentioning
confidence: 99%